Measurement of single top-quark production in association with a W boson in the single-lepton channel at √s=8 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Antel, Claire; Dunford, Monica; Anders, Christoph; Bolz, Arthur; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; Kolb, Mathis; et al. (The European physical journal. C, Particles and fields, 2021)
The production cross-section of a top quark in association with a W boson is measured using proton-proton collisions at $$\sqrt{s} = 8\,\text {TeV}$$. The dataset corresponds to an integrated luminosity of $$20.2\,\text {fb}^{-1}$$, and was collected in 2012 by the ATLAS detector at the Large Hadron Collider at CERN. The analysis is performed in the single-lepton channel. Events are selected by requiring one isolated lepton (electron or muon) and at least three jets. A neural network is trained to separate the tW signal from the dominant $$t{\bar{t}}$$background. The cross-section is extracted from a binned profile maximum-likelihood fit to a two-dimensional discriminant built from the neural-network output and the invariant mass of the hadronically decaying W boson. The measured cross-section is $$σ _{tW} = 26 ± 7\,\text {pb}$$, in good agreement with the Standard Model expectation.